STADIUM HIV/AIDS DAN TINGKAT STRES: KORELASI KEDUANYA - Ahmad Ikhlasul Amal; Retno Setyawati (Jurnal Ilmiah Keperawatan, 2021)
Background: Infectious diseases that are still of concern to many circles, namely HIV / AIDS. This is confirmed by the reason that there is still an increase in the number of cases. In addition, this disease makes sufferers or people who are often known as people living with HIV / AIDS (PLWHA) experience both physical and psychological problems. The physical problems experienced by PLWHA, of course, depend on the stage of the patient's disease. PLWHA who experience physical problems may experience stress due to their illness. The purpose of this study was to determine the relationship between HIV stage and stress levels. Method: This type of research is a quantitative observational study with a correlation analytic design with consecutive sampling technique. Data collection was carried out by using a questionnaire with the number of respondents as many as 38 people. The data obtained were processed statistically using the Spearmen Rho statistical test. Results: based on the data, it was found that from 38 research respondents, most of them were 20-60 years old (76.3%). The majority of people with HIV / AIDS were male, namely 23 people (60.5%) with most of the occupations of HIV / AIDS sufferers being private (63.2%). Respondents' HIV was at stage II (50%) and III (50%). The level of stress experienced by HIV / AIDS sufferers is quite good, namely: at level I (31.57) and II (68.43). r = -174, p-value = 0.283. Conclusion: there is no correlation between HIV stage and stress level.